Targeting cisplatin resistance in breast cancer using a combination of Thymoquinone and Silymarin: an in vitro and in vivo study - Reem Ali Hamed; Wamidh H. Talib (Pensoft Publishers, 2024)
Background: Breast cancer (BC) is considered the most diagnosed cancer among women globally. This is because of its high possibility of metastasis and high resistance to chemotherapy. Cisplatin is a platinum-based antitumor agent that is used to treat various types of cancer. However, the main obstacle to using this drug is drug resistance. Drug resistance is a cause of most relapses of cancer which eventually lead to death. Nowadays, combining natural products is a trend to overcome drug resistance. Thymoquinone (TQ) is a natural phytochemical that exists mainly in blackseed. It has been used in medicine for decades, especially as an anticancer agent. Silymarin is a milk thistle compound that exhibits anticancer, hepatoprotective, and neuroprotective activity. Hence, the combination of TQ and silymarin could be a probable solution to treat cancer and reduce chemoresistance. Methods: This study tested this combination on cisplatin-sensitive (EMT6/P) and cisplatin-resistant (EMT6/CPR) mouse mammary cell lines. Apoptotic and antiproliferative activity was assessed for TQ and silymarin in vitro using caspase-3 and [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide] (MTT) assays, respectively. An in vivo study was performed to evaluate the effect of TQ and silymarin combination in mice inoculated with EMT6/P and EMT6/CPR cells. The safety profile was also examined using creatinine and liver enzyme assays. Results: In vitro, the TQ and silymarin combination synergized in both cell lines. Also, this combination caused apoptosis induction at a higher rate than the single treatment in both cell lines. In vivo, TQ and silymarin combination resulted in a remarkable reduction in tumor size and enhanced the cure rate in mice implanted with EMT6/P and EMT6/CPR cell lines. According to the safety profile results, TQ and silymarin combination was safe. Conclusion: In conclusion, the combination of TQ and silymarin provides a promising solution in treating BC resistant to cisplatin by inducing apoptosis. Further studies are needed to define the exact anticancer mechanisms of this combination.